?-tubulin complexes: size does matter. - Jeng, R.; Stearns, T. (Trends in Cell Biology, 1999)
gamma-Tubulin is a conserved component of all microtubule-organizing centres and is required for these organelles to nucleate microtubule polymerization. However, the mechanism of nucleation is not known. In addition to its localization to organizing centres, a large pool of gamma-tubulin exists in the cytoplasm in a complex with other proteins. The size of the gamma-tubulin complex and number of associated proteins vary among organisms, and the functional significance of these differences is unknown. Recently, the nature of these gamma-tubulin complexes has been explored in different organisms, and this has led us closer to a molecular understanding of microtubule nucleation.